2016
DOI: 10.1186/s12883-016-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum myokines and aerobic exercise training in patients with spinal cord injury: an observational study

Abstract: BackgroundPatients with spinal cord injury (SCI) have a higher prevalence of cardiovascular diseases compared to the healthy population. Aerobic exercise training is one of the recommended treatments. However, literature regarding the effect of aerobic training on patients with SCI is scarce. This study evaluated changes in parameters of exercise physiology and serum myokines immediately after exercise and after a training program among patients with SCI.MethodsMale patients with SCI and age- and sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…29 The positive association between myostatin and HGS observed in our patients must be discussed. The positive association observed between myostatin and HGS in different populations is still debated in the current literature, with some authors showing negative or no associations [30][31][32][33][34][35][36][37][38] and others showing a positive one. 11,[39][40][41][42][43] Such discrepancies in the literature could be explained, at least in part, by the difference in assays used to measure myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…29 The positive association between myostatin and HGS observed in our patients must be discussed. The positive association observed between myostatin and HGS in different populations is still debated in the current literature, with some authors showing negative or no associations [30][31][32][33][34][35][36][37][38] and others showing a positive one. 11,[39][40][41][42][43] Such discrepancies in the literature could be explained, at least in part, by the difference in assays used to measure myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Results of most recent studies suggest that physical exercise attenuates myostatin gene and protein expression in skeletal muscles directly after training [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ], while a decrease of physical activity achieved by daily step reduction increased myostatin mRNA expression [ 135 ]. In most studies, serum myostatin levels were found to increase acutely after various exercise types (ultramarathon, aerobic, resistance and high-intensity training) [ 136 , 137 , 138 , 139 , 140 , 141 ], and decrease in the long term as a result of physical training [ 90 , 142 , 143 , 144 , 145 , 146 ]. Two studies noted an increase in circulating myostatin concentrations as a result of various (strength training, balance training, stretching exercises, walking recommendations) physical exercise over very long periods (6 and 12 months) [ 80 , 93 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…With convenience sampling, individuals may not be representative of the larger population, thus, affecting both internal and external validity. Of the studies included, 32% (n = 10) used convenience sampling [3,4,6,9,10,12,14,18,19,23] (37% of non-case studies) while the remaining 68% (n = 21) did not report their sampling method (63% of non-case studies) [1, 5, 15, 20, 22, 25, 26, 28-30, 32, 34, 35, 37-41, 43, 44, 46]. Collectively, low sample size and convenience sampling limit the generalizability of findings to the SCI population as a whole.…”
Section: Sampling Issuesmentioning
confidence: 99%
“…Specifically, adequate control groups minimize the degree to which bias is involved in conducting and analyzing a study, affect the endpoints that can be studied, and ensure that the interventional effects are beyond normal variation to prevent under-or over-estimation of study effects [16]. Only 58% (n = 18) of the studies examined, and 67% of non-case studies, included a comparison group [1,3,6,9,12,15,20,22,23,25,26,30,33,34,38,40,41,43]. Additionally, only 67% (n = 12) of studies that included a comparison group were appropriately matched (examples: age, injury duration, etc.)…”
Section: Lack Of An Appropriate Control Groupmentioning
confidence: 99%
See 1 more Smart Citation